2020
DOI: 10.34172/jcvtr.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of cholesteryl ester transfer protein (CETP) TaqIB gene polymorphism and canola, sesame and sesame-canola oils consumption on metabolic response in patients with diabetes and healthy people

Abstract: Introduction: Cholesteryl ester transfer protein (CETP) is a key regulating enzyme in the lipid metabolism pathway, and its gene polymorphism may be a candidate for modulating the metabolic responses to dietary intervention. We thus examined whether the effects of the CETP TaqIB polymorphism on metabolic profiles were modified by dietary plant oils. Methods: This is a retrospective analysis of data collected during a randomized triple-blind cross over trial. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…It was observed that intake of olive oil-enriched skim milk resulted in a larger increase in HDL and a decrease in LDL:HDL ratio in participants with 'B1B1' genotype compared to those carrying the 'B2' allele (mean change in HDL (mmol/l) (95% confidence interval): 0.179 (0.096 to 0.262) for 'B1B1' vs 0.089 (0.032 to 0.146) for carriers of 'B2', P interaction < 0.0010; mean change in LDL:HDL ratio (mmol/l) (95% confidence interval): −0.470 (−0.729 to 0.211) for 'B1B1' vs −0.097 (−0.275 to 0.081) for carriers of 'B2', P interaction < 0.0010). While these studies show that individuals with the 'B1B1' genotype could benefit from consuming these diets, the interactions were reported only in those with either T2D [61] or hypercholesterolemia [43,62] indicating that these results may not apply to healthy participants and hence, this limits the wider application of the findings.…”
Section: Taqib (Snp Rs708272 G > A)mentioning
confidence: 91%
See 2 more Smart Citations
“…It was observed that intake of olive oil-enriched skim milk resulted in a larger increase in HDL and a decrease in LDL:HDL ratio in participants with 'B1B1' genotype compared to those carrying the 'B2' allele (mean change in HDL (mmol/l) (95% confidence interval): 0.179 (0.096 to 0.262) for 'B1B1' vs 0.089 (0.032 to 0.146) for carriers of 'B2', P interaction < 0.0010; mean change in LDL:HDL ratio (mmol/l) (95% confidence interval): −0.470 (−0.729 to 0.211) for 'B1B1' vs −0.097 (−0.275 to 0.081) for carriers of 'B2', P interaction < 0.0010). While these studies show that individuals with the 'B1B1' genotype could benefit from consuming these diets, the interactions were reported only in those with either T2D [61] or hypercholesterolemia [43,62] indicating that these results may not apply to healthy participants and hence, this limits the wider application of the findings.…”
Section: Taqib (Snp Rs708272 G > A)mentioning
confidence: 91%
“…Statistically significant interactions between carriers of the 'B1' allele and dietary factors were reported by three dietary intervention studies [43,61,62]. In a randomised triple-blind crossover trial performed in 95 Iranian patients with T2D and 73 healthy controls using three diets: sesame oil, canola oil and sesame-canola oil [61], it was demonstrated that, in the T2D group, those with 'B1B1' genotype had a significant reduction in lipid ratios after consuming sesame oil and sesame-canola oil (change in LDL:HDL (mg/ dl): −1.29, P interaction = 0.0270; change in TC:HDL (mg/dl): −2.82, P interaction = 0.0240; and change in TG:HDL (mg/ dl): −7.00, P interaction = 0.0250) but there were no reports of significant reductions in lipid ratios in participants carrying the 'B2' allele.…”
Section: Taqib (Snp Rs708272 G > A)mentioning
confidence: 99%
See 1 more Smart Citation
“…29 The results of our parent project 30 on other health-related aspects have been reported elsewhere. 29,[31][32][33] Because the metabolic responses to dietary interventions may differ between healthy individuals and those with chronic diseases, we examined the effects of dietary CO, SO and SCO on body weight and composition, which were assessed as secondary outcomes in a large controlled clinical trial conducted in patients with T2DM. In addition, although sex-specific effects are well acknowledged in some area of research, 34 they are not sufficiently elucidated in nutrition research studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it is reported that MUFAs beneficially affect Apo A‐1, but no significant effect of CO on this marker was indicated (Negele et al, 2015). It should be noted that some genetic polymorphisms might interact with dietary oils in their effect on cardiometabolic markers (Ramezani‐Jolfaie et al, 2020a; Ramezani‐Jolfaie et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%